Assessment of the effect of borax and boric acid additives in cutting fluids on milling of AISI O2 using MQL system - Kurşuncu, Bilal; Yaraş, Ali; Kurşuncu, Bilal; Yaraş, Ali (Springer London Ltd, 2018)
The present study assesses the effects of eco-friendly cutting fluids prepared on cutting performance and tool wear in hard milling of AISI O2 cold work tool steel applying the minimum quantity lubrication (MQL) technique for sustainable manufacturing. Boron compounds such as boric acid (BA) (5% wt.) and borax (BX) (5% wt.) as additives were added to ethylene glycol (EG) of base fluid. For the purpose of comparison, commercial boron oil was utilized in addition to the dry machining as a benchmark using MQL method. The lowest surface roughness value (0.411 mu m) was reached in the cutting fluid containing BA. Compared with the dry condition, the surface roughness value was determined to be improved as 52 and 38% in cutting fluids containing BA and BX, respectively. The highest tool life was measured as a cutting length of 3.15 m in the cutting fluid containing BX. According to the experimental results, a raise of tool life occurred in cutting fluids prepared using both BA and BX. Compared with dry condition, tool life was increased by 110% with cutting fluid prepared by BA and by 50% by cutting fluid prepared by BX. The cutting forces decreased with cutting fluids containing both boron compounds. After milling process, the wear type and mechanism of the cutting tool were analyzed by scanning electron microscopy (SEM) aided with energy dispersive spectroscopy (EDS). Furthermore, it has been found that the diffusion and abrasion are dominant wear mechanisms on cutting tools, all the cutting fluids studied. Consequently, the promising results were obtained by adding boron compounds, which are harmless and non-toxic to human and environmental health, to cutting fluid-based EG for improving machinability of AISI O2 cold work tool steel.
Keywords: Minimum Quantity Lubrication; Hardmilling; Boric Acid; Borax; Aisio2; Tool Wear; Cutting Performance